The effect of flexitarian diets on high-densit- lipoprotein (HDL) serum in obese female students - Rubyanti, Septiana Dwi; Margawati, Ani; Afifah, Diana Nur; Dieny, Fillah Fithra (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Obesity in female students affects metabolic profiles and reproduction. Consuming a plant-based diet can inhibit the synthesis of fatty acids and cholesterol, thereby reducing the risk of obesity. The lipid profile plays a crucial role in metabolism and includes high-density lipoprotein (HDL), which has a protective effect against cardiovascular disorders, obesity, hypertension, and dyslipidemia.Objective: To analyze the effect of flexitarian diets on changes in serum HDL levels in obese female students.Methods: A quasi-experimental design with pre-post-test control group was employed. Twenty-two female students aged 19-25 years were selected using consecutive sampling. The subjects were divided into intervention and control groups. The intervention group received a flexitarian diet for 4 weeks consisting of three meals and two snacks totaling 1500 calories per day. Both groups were provided with educational leaflets about obesity and balanced nutrition. Food intake was assessed using a 3x24-hour food recall, while physical activity was measured using the IPAQ-SF questionnaire. Serum HDL levels were analyzed enzymatically before and after the intervention. Statistical analysis was conducted using SPSS 25, including the Shapiro-Wilk test for normality, paired t-tests, independent t-tests, and the Mann-Whitney test.Results: There was a significant decrease in serum HDL levels in the intervention group (2.00 ± 2.83 mg/dL), while serum HDL levels in the control group increased (3.27 ± 8.25 mg/dL), although this increase was not statistically significant. There was no significant difference between the two groups in terms of the mean change in HDL levels (p > 0.05).Conclusion: A flexitarian diet for 4 weeks can lead to a significant reduction in serum HDL levels.